THE EVOLUTION OF GENDER FLUIDITY AND PERFORMATIVITY IN POSTMILLENNIAL INDIAN HINDI CINEMA - Srivastava, Prerna; Shekhawat, Kiran; Noval, Sangeetha; Choudhary, Ritu Raj; Jhajharia, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Over time, contemporary post-modernist writers and directors have begun to interrogate authority, stereotypes, and sexist values, challenging the foundations of social practices that underpin the old binary model of sex or gender. This study examines the development of gender fluidity and performativity in postmillennial Indian Hindi Cinema, evaluating how contemporary filmmakers are interrogating gender binaries and presenting more comprehensive depictions, dismantling the gender distinctions, emotional perceptions, and emotional facilitation of thoughts and understanding. The paper examines the cinematic elements of costume design, character growth, visual elements, and plot, finding out how they support to the explanation of non-binary characters and gendered spaces. The paper is based on the theory of gender performativity as by Judith Butler and the concept of gendered space, but it critically evaluates the films that challenge the heteronormative conventions by redefining masculinity, femininity and queer identities. It also examines the intersection of gender, class, and caste, exploring how cinema converts power constructions and social hierarchies through developing gender depictions. By analysing revolutionary films such as Lipstick Under My Burkha and Kapoor & Sons, this study underscores Bollywood’s rising role in analysing gender standards and nurturing inclusivity. The study contributes to the broader discourse on gender inclusivity, cinematic revolution and the role of media in determining progressive social attitudes in India and beyond.